Association between cranial asymmetry severity and chronic subdural hematoma laterality - Hsieh, Cheng-Ta (Neurosciences (Riyadh), 2020)
OBJECTIVES: To analyze the association between cranial asymmetry severity and chronic subdural hematoma (CSDH) laterality. METHODS: We retrospectively assessed 120 patients with surgically treated unilateral CSDH from January 2009 to December 2018. Preoperative computed tomography images were used to determine occipital vault angles, bilateral cranium areas, and cranial index of symmetry (CIS) ratios. RESULTS: The male sex (70%) was the predominant factor promoting CSDH pathogenesis. In the overall study population (mean age, 71.3 years; left-sided CSDH, 58/120 [48%] patients; right-sided CSDH due to right-sided flat cranium, 38 patients; left-sided CSDH due to right-sided flat cranium, 37 patients). Flat cranial asymmetry was nonsignificantly associated with CSDH laterality (p- value=.689). However, most CSDH patients (86.7% of 120 patients) presented dominant-sided nonoverlapping areas on the left side. Thirteen (81.3%) patients presenting right-dominant nonoverlapping areas had right-sided CSDH, and 55 (52.9%) patients had left-dominant nonoverlapping area had left-sided CSDH (p- value=0.01). The CIS ratio was significantly higher in patients with right-dominant nonoverlapping areas than in those with left-dominant nonoverlapping areas (97.2% vs 95.9%, p- value<0.0001). CONCLUSION: Left-sided hematoma predominance is not associated with a flat cranium and laterality of unilateral CSDH. Moreover, more asymmetric crania with lower CIS ratios may predict left-sided CSDHs, whereas the right-sided CSDHs may be more common in symmetric crania with higher CIS ratios. The CSDH laterality is potentially attributable to cranial asymmetry severity.